BEHAVIORAL INTENTION TO PAY ZAKAH ON EMPLOYMENT INCOME AMONG ACADEMICIANS IN KANO STATE, NIGERIA - Dandago, Kabiru Isa; Muhammad, Aliyu Dahiru; Abba, Safiyya Abubakar (Bank Indonesia, 2016)
The institution of zakah is the cornerstone of the Islamic economic system and the disbursement of the zakah fund in line with the Qur’anic injunction ensures equitable distribution and transfer of wealth from the rich to the poor. However, zakah practice in many Muslim countries left wide gap especially in realizing the goal of zakah in poverty reduction. For instance, zakah on employment income is largely neglected despite its juristic backing and changing economic structure that creates high professional income earners that form either upper middle class or lower middle class of the society. The objective of this paper is to explore the intention of income earners to pay zakah on their employment income in Kano State as this will add to the zakatable sources of the State Zakah commission. The paper employed Theory of Reasoned Action to examine the behavioral intention of 300 academics across Kano state government owned tertiary educational institutions to pay zakah on their income. Structural equation modeling was used to analyze the data collected. The overall result shows that the respondents have favorable behavioral intention towards payment of zakah on employment income. Specifically, the positive effect of both attitudinal beliefs and subjective norm on the behavioral intention is revealed. Hence, the need to come up with a comprehensive policy that will boost zakah collection, consequently its distribution to reduce extreme poverty in the state.